The reality of teaching strategies used by Arabic language teachers in the primary stage to develop their students’ self-learning skills - Al-Sulami, Nawaf Saleh; Al-Harbi, Amal Nasser (Journal of Curriculum and Teaching Methodology, 2024)
This research aimed to identify the current teaching strategies used by Arabic language teachers at the elementary level to develop self-learning skills among their students. The researcher employed the descriptive-analytical method, and the research tool was a questionnaire applied to a random sample of 133 Arabic language teachers at the elementary level in Medina. The results revealed the current strategies used by Arabic language teachers to develop self-learning skills among their students, indicating that they practice cognitive teaching strategies with an average of 3.34 out of 4 and metacognitive teaching strategies with an average of 3.28. The "discussion and dialogue" strategy ranked first with an average of 3.57; all with an evaluation of "always." Based on the results, the researcher recommended training Arabic language teachers to use strategies that enhance self-learning skills among students through training programs and workshops. Furthermore, the necessity of implementing the programmed learning strategy and the small teacher strategy in teaching Arabic in elementary schools in the Kingdom of Saudi Arabia was highlighted, as the results showed these strategies were the least used by the teachers.
Keywords: teaching strategies; Arabic language teachers; skills for self-learning